Validity of effective medium theory in multilayered hyperbolic materials. (August 2017) - Zhang, Richard Z.; Zhang, Zhuomin M.
Abstract: Metal-dielectric multilayers can be designed to exhibit remarkable optical properties, including negative refraction for subwavelength superlensing. In this study, the applicability of the medium-homogenized effective medium theory (EMT) in place of multilayered thin-film optics is examined. Three metal-dielectric material and thin film thickness combinations that give rise to hyperbolic dispersion in different spectral regions are considered. In addition to investigating the radiative properties, the energy streamline method is used to determine the refraction angle and lateral displacement of rays. The electromagnetic fields inside the films are depicted to illustrate the coherent effect or the lack thereof. The radiative penetration depth is profiled to understand the effectiveness and limits of such multilayers in optical manipulation. The conditions and mechanism for the breakdown of EMT are elucidated in this case study.